Analisis Keterlibatan Orang Tua Dalam Proses Pembelajaran Terhadap Kesiapan Anak Memasuki Jenjang Sekolah Dasar (SD) Di PAUD Nurul Aulad Pancalaksana - Aan Anipah; Inten Risna (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to analyze parental involvement in the learning process and its influence on children’s readiness to enter primary school at PAUD Nurul Aulad Pancalaksana. Children’s readiness is understood as a holistic condition encompassing cognitive, language, social-emotional, independence, and learning attitude aspects. This research employed a qualitative approach with a descriptive design. The research participants consisted of parents and early childhood teachers selected through purposive sampling. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing, with data credibility ensured through source and technique triangulation. The findings indicate that parental involvement manifested in home learning assistance, character building, positive communication, and active participation in school activities significantly contributes to children’s readiness for primary education. Children who receive consistent parental support demonstrate better cognitive readiness, more mature social-emotional development, greater independence, and positive attitudes toward learning. This study emphasizes that strengthening partnerships between parents and schools is a key strategy in supporting a smooth, child-friendly, and development-oriented transition from early childhood education to primary school.